2013
DOI: 10.4049/jimmunol.1202951
|View full text |Cite
|
Sign up to set email alerts
|

IL-2–Independent and TNF-α–Dependent Expansion of Vβ5+ Natural Regulatory T Cells during Retrovirus Infection

Abstract: Friend virus (FV) infection of mice induces the expansion and activation of regulatory T cells (Tregs) that dampen acute immune responses and promote the establishment and maintenance of chronic infection. Adoptive transfer experiments and the expression of Neuropilin 1 indicate that these cells are predominantly natural Tregs rather than virus-specific conventional CD4+ T cells that converted into induced Tregs. Analysis of Treg TCR Vβ chain usage revealed a broadly distributed polyclonal response with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 82 publications
6
59
0
Order By: Relevance
“…Surprisingly, no expansion or activation of Tregs was found in the spleens of acutely mCMV-infected mice, in contrast to what is described for FV or lymphocytic choriomeningitis virus (LCMV) infection ( Fig. 1b and c) (10)(11)(12). Additionally, no expansion of the V␤5 ϩ CD4 ϩ Foxp3 ϩ Tregs, which recognize self-superantigens expressed by endogenous mouse mammary tumor virus, were detectable in mCMV-infected mice (8,10,11; data not shown).…”
Section: It Is Still Unclear Whether Expanded and Activated Regulatormentioning
confidence: 43%
See 3 more Smart Citations
“…Surprisingly, no expansion or activation of Tregs was found in the spleens of acutely mCMV-infected mice, in contrast to what is described for FV or lymphocytic choriomeningitis virus (LCMV) infection ( Fig. 1b and c) (10)(11)(12). Additionally, no expansion of the V␤5 ϩ CD4 ϩ Foxp3 ϩ Tregs, which recognize self-superantigens expressed by endogenous mouse mammary tumor virus, were detectable in mCMV-infected mice (8,10,11; data not shown).…”
Section: It Is Still Unclear Whether Expanded and Activated Regulatormentioning
confidence: 43%
“…1b and c) (10)(11)(12). Additionally, no expansion of the V␤5 ϩ CD4 ϩ Foxp3 ϩ Tregs, which recognize self-superantigens expressed by endogenous mouse mammary tumor virus, were detectable in mCMV-infected mice (8,10,11; data not shown). Furthermore, Tregs from mCMV-infected mice displayed the same phenotype as Tregs from naive animals (Fig.…”
Section: It Is Still Unclear Whether Expanded and Activated Regulatormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we demonstrated that FV infection induced disproportionately greater expansion of Tregs expressing the T cell receptor (TCR) Vβ5 chain compared to Tregs expressing other Vβ chains (17). Investigation revealed that the proliferation of this subpopulation was driven by a mechanism distinct from other Tregs.…”
Section: Introductionmentioning
confidence: 99%